Global Perspectives on Learning Analytics in K12 Education - Aguerrebere Cecilia; He Hao; Kwet Michael; Laakso Mikko-Jussi; Lang Charles; Marconi Cecilia; Price-Dennis Detra; Zhang He (The Society for Learning Analytics Research (SoLAR), 2022)
The utilization of learning analytics within K12 education has expanded over the last ten years. The availability of new software for both administering school systems and tools for teaching has increased and with it the amount of data collected and analyzed. However, each country is on a different path with respect to how it navigates the availability of these new technologies and the data they produce. Given the heterogeneity of systems, practices and cultures, rather than attempt to comprehensively document learning analytics the following chapter asked six scholars involved in K12 learning analytics research to document what they see as the key benefits and concerns associated with learning analytics within their country. The countries represented are China, Finland, South Africa, Uruguay and The United States of America. Although each is clearly different, a common theme emerges around the difficulties and dangers of moving education systems from data collection to data utilization.
Handbook of Learning Analytics